Digital Transformation in the Hotel Industry: A Study of Four-Star Hotels in Szeged - Mondok, Anita (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
With the evolution of technology, the landscape of hotel management is set to undergo a remarkable transformation, reshaping operations and enhancing guest experiences like never before. This study investigates the pervasive impact of technology on hotel management and customer experience. The main goal is to explore the various ways digital innovations are revolutionizing guest services and enhancing operational efficiencies in the hotel industry responding to the highly volatile external environment. The secondary research part relied on literature review, predominantly sourced from electronic publications, press releases, and systematic website content evaluation. The market phenomena were examined through interviews with hotel managers of four-star hotels in Szeged. The findings indicate that enterprises in the centre of Southern Great Plain region (Hungary) have adopted IT-based solutions to enhance market efficiency to differing extents. The study identifies improvements in operational efficiency driven by IT-based solutions; however, guest-facing digital innovations remain limited. The study examined 11 units with official rating, enabling the results to be contextualised inside a specific market, while underscoring those trends identified internationally in small open economies are swiftly manifesting locally. The innovation of the research is in its market adaption and serves as a benchmark resource for hotel decision makers.